PENERAPAN STANDAR KOMPETENSI JURNALIS I-NEWS BIRO MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research discusses how journalists i-News Makassar Bureau apply the competency model that a journalist must have in accordance with the Press Council Regulation No. 1 / peraturan-DP / II / 2010 regarding journalist competency standards, as well as how to standardize journalists' competence in i-News bureau. Makassar. The results of this study indicate; 1) i-News journalists from the Makassar bureau have understood and applied what is the model and competency category of a journalist, as well as what is stated in the press council regulations regarding journalist competency standards, i-News bureau Makassar journalists are also aware of ethics and law based on the code journalistic ethics in order to carry out their duties as well as possible. 2) However, in terms of standardization of competency of journalists, i-News, the Makassar bureau is still not fully competency tested, this is motivated by several factors such as the i-News bureau Makassar company does not require journalists to have competency tested status, and a lack of motivation from within the journalist. alone.